Physical and mechanical properties of wood from invasive tree species - Szabolcs, Komán; Varga, David (Maderas. Ciencia y Tecnología, 2020)
Because invasive tree species are being suppressed all over the world, there is a lack of basic information needed for their use in the processing industry. One piece of important information for woodworking applications is the air-dry density, which is 653 kg/m3 in the case of tree of heaven (Ailanthus altissima), 536 kg/m3 for box elder (Acer negundo), and 702 kg/m3 for green ash (Fraxinus pennsylvanica). The order of the 3 species is the same for oven-dry and basic density. In terms of compression and bending, tree of heaven has higher values than green ash. Because the strength of the tree of heaven and the green ash are largely the same as the common ash (Fraxinus excelsior), it can be replaced by these tree species. The properties of box elder wood are significantly different from those of